Degradation Comparison of Cyclic and Linear Siloxane Contamination on Solid Oxide Fuel Cells Ni-YSZ Anode - Tian, Jiashen; Milcarek, Ryan J. (Frontiers in Energy Research, 2021)
The solid oxide fuel cell (SOFC) nickel-yttria stabilized zirconia (Ni-YSZ) anode degradation due to different types of siloxane contamination is investigated. A cyclic structure siloxane, octamethylcyclotetrasiloxane (D4), and a linear structure siloxane, decamethyltetrasiloxane (L4), are mixed with H2+N2 as the fuel for SOFCs at 750 °C. The electrochemical characterization results after stability experiments suggest that the SOFC contaminated with cyclic siloxane, D4, had higher degradation. Pure YSZ pellets with different surface hydroxylation extents were also tested to investigate the D4/L4 adsorption and deposition process. Postmortem SEM/WDS, XRD and Raman analysis all indicate that cyclic siloxane has more deposition than linear siloxane on the anode. Further analysis demonstrates that high adsorption and low desorption rates of cyclic siloxane on YSZ are linked to the degradation. Besides the silicon deposition, SiC and amorphous carbon deposition were also observed from the XRD and Raman analysis.